Energy Saving Theoretical Principles and Their Technological Implementation in High-Temperature Production of Building, Household and Technical Ceramics - Fedorenko, Olena Yu.; Pitak, Yaroslav M.; Kartyshev, Serhii V.; Kapustenko, Petro (c/o AIDIC, 2023)
The priority areas for the development of different purposes ceramics technology are the energy-saving technologies creation and the reduction of production energy costs. The main efforts should be directed to the implementation of energy-saving reserves at the firing stage of products as the most energy-intensive technological operation. The necessity of temperature reduction and the firing time shortening requires special attention to the ceramic masses and glazes prescripts, designed to ensure high-quality products under energysaving firing conditions. This paper considers the new approach for low-temperature masses and frit-free glaze development and presents an algorithm for composition designing in the production of building, technical and household ceramics. Examples of the original and low-cost method used for the energy-saving reserves implementation in porcelain slabs, electrical, sanitary and tableware porcelain production are given. The effectiveness of the proposed method was experimentally confirmed. Its use made it possible to reduce the firing temperature of products by 100-150 °C, significantly shorten the production cycle and, as a result, reduce energy costs by 15-20 %.
Keywords: ceramics; temperature; electric energy; gas-fired kilns; chemical reactions